Populism in popular literature: the political rhetoric of the ‘people’ in Indonesian bestseller novels - Rika Yani (CV Narasi Khatulistiwa Indonesia, 2026)
Background: The convergence of populist discourse and popular culture in post-Reformasi Indonesia positions bestselling novels as key sites for political meaning-making. Objective: This study examines how Indonesian bestseller novels construct “the people,” oppose elites, and normalize populist logic. Method: A qualitative approach integrates Critical Discourse Analysis, narrative analysis, and populist rhetoric. Results: Novels portray “the people” as morally virtuous against corrupt elites, using polarized discourse, emotional narratives, and simplified rhetoric to legitimize populist views. Implication: These findings show that popular literature functions as a cultural infrastructure shaping everyday political imagination. Novelty: This study provides an integrative framework linking discourse, narrative, and populist rhetoric to reveal how literary texts normalize populism beyond formal politics.